2013
DOI: 10.17265/1537-1506/2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Does Market Timing Affect Capital Structure?: Evidence for Chinese Firms

Abstract: This paper investigates the market timing hypothesis of capital structure using a sample of 1,077 Chinese firms for the period 1992 to 2007. We find that market timing plays a significant role in capital structure decisions. However, market timing effects are not persistent and disappear within three years. The results suggest the prominent role played by the government in timing of security issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The findings, however, indicated that in China, there was a persistent effect of market timing on CS. Hence, Russel and Hung's (2013) findings differ from Ma and Rath's (2016) findings.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The findings, however, indicated that in China, there was a persistent effect of market timing on CS. Hence, Russel and Hung's (2013) findings differ from Ma and Rath's (2016) findings.…”
Section: Introductionmentioning
confidence: 74%
“…Using a sample from 1992 to 2007, Russel and Hung (2013) obtained the results that the historical marketto-book ratio of the previous year measured using a yearly timing proxy and it had a negative effect on BL at IPO+3, whereas using a long-term timing proxy, it had a positive effect on BL at an IPO+2 up to IPO+10. This finding concluded that there was no persistent effect of market timing on CS in China.…”
Section: Introductionmentioning
confidence: 99%
“…Russel and Hung studied Chinese firms from 1992 to 2007 and finds that the effects are evident in the first few years but disappear after IPO + 3. However, Russel and Hung do recognize that the dynamics of the Chinese market could be influenced by government regulations on the timing of security issuance and market timing cannot be effectively performed; thus, influencing its impacts on capital structure [12]. Nevertheless, Chinese data is not unaccompanied.…”
Section: Market Timing Theorymentioning
confidence: 99%
“…This theory was conceptualized by Baker and Wurgler (2002) to find cheaper types of financing regardless of their current internal resources, debt levels, and equity capital. A growing number of studies have applied this theory to explain the capital structure of companies during the global financial crisis (Bolton et al, 2013;Russel & Hung, 2013). According to Wang et al (2007), the marketing timing theory is the main determinant of the financial policy of a company and has a lasting impact on the management of working capital.…”
Section: Market Timing Theorymentioning
confidence: 99%
“…The marketing timing theory is the main determinant of the financial policy of a company and has a lasting impact on the management of working capital during the global financial crisis (Bolton et al, 2013;Russel & Hung, 2013).…”
Section: Market Timing Theorymentioning
confidence: 99%